Overcoming major barriers in seed ecology research in developing countries - Silveira, Fernando A. O.; Fuzessy, Lisieux; Phartyal, Shyam S.; Dayrell, Roberta L. C.; Vandelook, Filip; Vázquez-Ramírez, Jerónimo; Tavşanoğlu, Çağatay; Abedi, Mehdi; Naidoo, Sershen; Acosta-Rojas, Diana C.; Chen, Si-Chong; Cruz-Tejada, Diana M.; et al. (Seed science research, 2023)
Scientists are becoming increasingly aware that disparities in opportunities for conducting and publishing research among scientists living under different socio-economic contexts have created pervasive biases and long-lasting impacts on our views of the natural world. These disparities are challenging the establishment of a global research agenda for a variety of disciplines, including seed ecology. Seed ecology has progressed enormously recently, but multiple barriers have hindered progress in the Global South where biodiversity and environmental complexity are highest. Here, we identify ten major challenges that seed ecologists from developing countries face in relation to planning, designing, conducting and publishing their research. We also propose several measures to overcome these challenges: (1) closing biodiversity knowledge shortfalls, (2) enhancing and creating long-term seed ecological networks, (3) supporting better infrastructure, (4) making fieldwork easier and safer, (5) unlocking funding opportunities, (6) promoting inclusive scientific meetings, (7) alleviating language barriers, (8) improving education, (9) shifting the notion of novelty and relevance and (10) supporting native seed markets. The authors recommend that the proposed solutions can be implemented by seed ecologists and the broader scientific community including funding agencies, research directors, journal editors and the academic publishing industry. Solutions can help mitigate multiple challenges simultaneously, thus offering a relatively inexpensive, fast and productive pathway for the development of seed ecology into a truly global research discipline that benefits scientists irrespective of their geographic location and background.